Traditional Malay House Architecture (Case Study of House of Datuk Amar Sridiraja in Tanjung Pura District, Langkat Regency) - Aisyah, Siti; Siregar, Yusra Dewi (Yupa: Historical Studies Journal, 2024)
This study aims to identify and analyze the form and architectural meaning of the traditional Malay house of Datuk Amar Sridiraja in Tanjung Pura, Langkat Regency. The house, which was built in 1827, is a cultural heritage that is still preserved today. The research method used is a historical approach with data collection techniques through direct observation, interviews with residents of the house, and literature studies. The results showed that Datuk Amar Sridiraja's house has Malay architectural characteristics that are reflected in elements such as stairs, doors, windows, poles, floors, ornaments, and roofs. Each of these elements has a symbolic meaning in Malay culture. The house's dominant yellow and green colors also have special meanings, symbolizing glory, majesty, and Islamic values. Although it has undergone several renovations, the house still retains the essence of traditional Malay architecture.